Assessment of naturally acquired neutralizing antibodies against rabies Lyssavirus in a subset of Nunavik's Inuit population considered most at risk of being exposed to rabid animals. (27th January 2019) - Ducrocq, Julie; Proulx, Jean‐François; Lévesque, Benoît; De Serres, Gaston; Wood, Heidi; Lemire, Mélanie
Abstract: Contact with infected saliva through the bite of a rabid animal is the main route of infection with the rabies Lyssavirus in humans. Although a few individuals have survived the infection, rabies remains the most lethal zoonotic infection worldwide. Over the last century, the dogma that rabies is invariably fatal has been challenged by the survival and recovery of infected animals. In humans, 11 studies have found rabies virus‐specific antibodies in unvaccinated individuals exposed to rabies virus reservoir species, suggesting the possibility of asymptomatic rabies virus infection, contact with non‐infectious virus or exposure to the virus without viral replication. Two of these studies were conducted in Arctic hunters. Considering the extensive exposure of Nunavik's Inuit to potentially infected animals through hunting, trapping, skinning and the preparation of Arctic carnivores, we analysed archived serum samples from the 2004 Nunavik Inuit Health Survey for the presence of rabies virus‐neutralizing antibodies (rVNA) in this sub‐population. A total of 196 participants who were considered at highest risk for exposure to rabies virus were targeted. Serum samples were tested for the presence of rVNA using a variation of the fluorescent antibody virus neutralization test, an assay recommended for the quantification of neutralizing antibody titres following vaccination. Our study identified two seropositive individuals among the 196 participants but a review of their medical record and a phone interview revealed previous vaccination. Our results do not provide evidence for naturally acquired rVNA in Nunavik's Inuit population.